ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KETERLAMBATAN PENYELESAIAN PEKERJAAN FISIK PADA PROYEK PNPM MANDIRI DI KOTA AMBON - Leuhery, Lenora (Jurnal Teknik Sipil, 2014)
National Program for Community Empowerment (PNPM Mandiri) that have been implemented in the city of Ambon since 2007, is believed to have contributed greatly to the city government in reducing poverty and improving social welfare. But one of the problems that a lot happening in the field is the delay in the completion of physical work on PNPM Urban city of Ambon, which is not optimal impact on the work and impeding the implementation of PNPM Mandiri, especially in terms of physical work completion PNPM Mandiri. This study aims to analyze the factors that cause delays in the completion of the physical work on the project in the city of Ambon PNPM Mandiri. The analysis was performed on the questionnaire respondents were represented from all parties involved in the project, namely PNPM employer / government (the owner), executing the work / community directly (KSM) and the executive supervisor jobs / employment coordinator (BKM). Performed with SPSS data processing and concluded that the factors that influence the occurrence of delays in completion of the work is the physical aspect Inspection Systems, Control and Evaluation of Work (X5), reporting on the indicators work slow and incomplete, with the percentage of agreement value of the intensity scale and the scale of determine respectively are: intensity scale (BKM 93%; KSM 97%; owners 95%) and determine the scale (BKM 96%; KSM 98%, owner 96%).